Factors that contributed works stress influencing teacher commitment: A study in sekolah menengah kebangsaan tanah merah(2) - Nurul Ain, Che Iberahim; Dayang Kartini, Abang Ibrahim (-, 2012)
The purpose of this research is to examine the factors that contributed works stress influencing teacher commitment in secondary school Tanah Merah(2).This study was conducted in secondary school Tanah Merah(2) in Kelantan. A total of 62 respondents were involved in this study. There are two hypotheses were tested in this study. The hypothesis was made based on the objectives of the study. This uses a quantitative method and questionnaire was used to gather feedback from respondents. This questionnaire covers demographic aspects of the respondents and the work stress factors is to examine workload and student misbehavior influencing teacher commitment. These factors are independent variables while teacher commitment is the dependent variable. Besides that, the questionnaire was also used to identify the dominant factors that influence teacher commitment. The results obtained showed no significant relationship between the two work stress factors of teacher commitment. In a nutshell, this research identify that some of the work stress factors is no interrelated with the teacher commitment. Apart from that, there are also recommendations that were contributed in this research for the school organization, teachers and future researchers who might be interested to have a broader research in the area.